The Influence of Financial Literacy, Financial Attitude, and Lifestyle on The Financial Behavior of Z Generation - Aprilia Karolina; Haryati Setyorini (Fokus Bisnis Media Pengkajian Manajemen dan Akuntansi, 2025)
Financial behavior refers to an individual’s decisions in managing finances, which reflect how a person plans, manages, and allocates financial resources. This study aims to examine the effect of financial literacy, financial attitudes, and lifestyle on the financial behavior of Generation Z, particularly in Surabaya. The number of respondents in this study was 100, with the criteria of being active university students, domiciled in Surabaya, aged 18 years and over, receiving monthly pocket money, and not living with their parents, such as living in boarding houses or dormitories. Respondent data were collected by distributing questionnaires using a purposive sampling technique. The data analysis technique used was SEM-PLS (Structural Equation Modeling-Partial Least Squares) with the SmartPLS 4.0 program. The results of this study indicate that financial literacy and lifestyle have no significant effect on financial behavior, while financial attitudes have a positive and significant effect on financial behavior.